A Sox17 downstream gene Rasip1 is involved in the hematopoietic activity of intra-aortic hematopoietic clusters in the midgestation mouse embryo - Gerel Melig; Ikuo Nobuhisa; Kiyoka Saito; Ryota Tsukahara; Ayumi Itabashi; Yoshiakira Kanai; Masami Kanai-Azuma; Mitsujiro Osawa; Motohiko Oshima; Atsushi Iwama; Tetsuya Taga (BMC, 2023)
Abstract Background During mouse embryonic development, definitive hematopoiesis is first detected around embryonic day (E) 10.5 in the aorta-gonad-mesonephros (AGM) region. Hematopoietic stem cells (HSCs) arise in the dorsal aorta's intra-aortic hematopoietic cell clusters (IAHCs). We have previously reported that a transcription factor Sox17 is expressed in IAHCs, and that, among them, CD45lowc-Kithigh cells have high hematopoietic activity. Furthermore, forced expression of Sox17 in this population of cells can maintain the formation of hematopoietic cell clusters. However, how Sox17 does so, particularly downstream signaling involved, remains poorly understood. The purpose of this study is to search for new Sox17 targets which contribute to cluster formation with hematopoietic activity. Methods RNA-sequencing (RNA-seq) analysis was done to identify genes that are upregulated in Sox17-expressing IAHCs as compared with Sox17-negative ones. Among the top 7 highly expressed genes, Rasip1 which had been reported to be a vascular-specific regulator was focused on in this study, and firstly, the whole-mount immunostaining was done. We conducted luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay to examine whether Sox17 regulates Rasip1 gene expression via binding to its enhancer element. We also analyzed the cluster formation and the multilineage colony-forming ability of Rasip1-transduced cells and Rasip1-knockdown Sox17-transduced cells. Results The increase of the Rasip1 expression level was observed in Sox17-positive CD45lowc-Kithigh cells as compared with the Sox17-nonexpressing control. Also, the expression level of the Rasip1 gene was increased by the Sox17-nuclear translocation. Rasip1 was expressed on the membrane of IAHCs, overlapping with the endothelial cell marker, CD31, and hematopoietic stem/progenitor marker (HSPC), c-Kit. Rasip1 expression was observed in most part of c-Kit+Sox17+ cells in IAHCs. Luciferase reporter assay and ChIP assay indicated that one of the five putative Sox17-binding sites in the Rasip1 enhancer region was important for Rasip1 expression via Sox17 binding. Rasip1 knockdown in Sox17-transduced cells decreased the cluster formation and diminished the colony-forming ability, while overexpression of Rasip1 in CD45lowc-Kithigh cells led to a significant but transient increase in hematopoietic activity. Conclusions Rasip1 knockdown in Sox17-transduced CD45lowc-Kithigh cells displayed a significant decrease in the multilineage colony-forming ability and the cluster size. Rasip1 overexpression in Sox17-untransduced CD45lowc-Kithigh cells led to a significant but transient increase in the multilineage colony-forming ability, suggesting the presence of a cooperating factor for sustained hematopoietic activity.